2020
DOI: 10.3390/antibiotics9090566
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Temporin A and Short Lipopeptides Combined with Gentamicin against Biofilm Formed by Staphylococcus aureus and Pseudomonas aeruginosa

Abstract: The formation of biofilms on biomaterials causes biofilm-associated infections. Available treatments often fail to fight the microorganisms in the biofilm, creating serious risks for patient well-being and life. Due to their significant antibiofilm activities, antimicrobial peptides are being intensively investigated in this regard. A promising approach is a combination therapy that aims to increase the efficacy and broaden the spectrum of antibiotics. The main goal of this study was to evaluate the antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…Moreover, their susceptibility depends on the biofilm maturity and the antibiotic used [ 98 ]. It was found that the antibiofilm activity of antibiotics (e.g., daptomycin, gentamicin) can be potentiated (synergistic effect) through supplementation with cationic antimicrobial peptides and lipopeptides [ 99 , 100 ]. Therefore, further studies should be extended to examine antibiofilm activity of gemini surfactants combined with antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, their susceptibility depends on the biofilm maturity and the antibiotic used [ 98 ]. It was found that the antibiofilm activity of antibiotics (e.g., daptomycin, gentamicin) can be potentiated (synergistic effect) through supplementation with cationic antimicrobial peptides and lipopeptides [ 99 , 100 ]. Therefore, further studies should be extended to examine antibiofilm activity of gemini surfactants combined with antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Temporins were initially isolated from the European red frog Rana temporaria , and nowadays they represent one of the largest groups of amphibian AMPs (more than 100 members) [ 15 , 16 ] and are among the shortest AMPs (only 10-13 residues) present in nature to date. While some isoforms (i.e., temporin A, (TA [FLPLIGRVLSGIL-NH 2 ]); temporin B (TB [LLPIVGNLLKSLL-NH 2 ]); temporin L (TL [FVQWFSKFLGRIL-NH 2 ]) of this family have already been characterized for their antimicrobial and cytotoxic properties [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], very little is known about the antimicrobial potential of temporin G (TG [FFPVIGRILNGIL-NH 2 ]) [ 25 ], which was isolated from the same frog specimen, especially against the bacterial biofilm phenotype. To the best of our knowledge, this is the first manuscript describing TG activity against preformed S. aureus biofilm as well as against persister cells.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the series of experiments, the minimum inhibitory concentrations (MICs) of the modified peptides were determined against strains of pathogenic methicillin-resistant S. aureus (MRSA), S. aureus, and P. aeruginosa (Table 2) [35,36]. As follows from Table 2, we found that the antimicrobial effect of the same peptides against various pathogenic microorganisms is comparable to the MIC (~1-5 µM) of the commercial antibiotic gentamicin sulfate [116,117].…”
Section: Antibacterial Activity Of Hybrid Amyloidogenic Peptidesmentioning
confidence: 87%